Character Education through Innovative Stories in Early Childhood - Leolita Puspitasari; Dhian Sitorukmi; Maghfira Kurnia Fajri; Moh Solehhudin (Proceeding International Symposium on Global Educatiorg Psychology, and Cultural Synergy, 2025)
Character education is considered crucial starting in early childhood because it is an educational process aimed at developing values, attitudes, and behaviors that reflect noble morals or noble character. Early childhood, or what psychologists call the golden age, is proven to be crucial for children's ability to develop their potential. Therefore, in children's character education, storytelling can be used to shape and develop it. This study aims to describe the application of character education through innovative stories in early childhood. The research method used is descriptive qualitative, with data collection techniques through observation and review of previous research. The results of the study indicate that the application of innovative stories is effective in instilling character values ​​in children. Teachers act as facilitators in guiding children's moral understanding through reflective activities after the story is presented. Thus, innovative stories can be an effective educational strategy in character formation in early childhood.